O Cancioneiro de Elomar: uma identidade sonora do sertão e suas performances. - Arruda, Lucas Oliveira de Moura (2015)
The aim of this research is to investigate the musical identity of Brazil’s northeastern backlands in Brazilian composer (from Vitória da Conquista – BA) Elomar Figueira Mello’s songbook (CANCIONEIRO). Also, the thesis has the purpose to analyze the modes by which this identity is expressed in the performances made by Elomar itself and by other performers of his music. For achieving this aim, I have built a corpus of five songs picked up from his CANCIONEIRO (that has in full 49 songs). The text develops itself around the analysis of these five songs, from four record sources: 1. the scores published in the collection CANCIONEIRO (2008); 2. the sound recordings of the songs made by the composer himself; 3. the sound recordings of the songs made by other performers; 4. transcriptions, carried out by myself, of the sound recordings made by other performers. Data gathering used sound-documentary research and fieldwork, with direct contacts with the artist, participant observation, personal or virtual contact with admirers and artists related to Elomar’s work. The thesis that results of the research is divided into four chapters, which bring to light eight characteristics of Elomar’s musical and artistic identity. At all, eight characteristics were identified: 1. the sonic-instrumental conception as a means of cultural resistance; 2. Elomar’s personal style in guitaristic execution; 3. employment of “typical” sounds of Brazilian Northeastern Backlands; 4. the relationship with cantoria (a Brazilian backland’s typical form of popular sung poetry); 5. border music; 6. the imaginary constituted around medieval art and literature; 7. the imagination of Elomar regarding the rural exodus due to the drought in the hinterland; 8. the personal option for an independent pathway in Brazilian music business.